Effect of high pressure on the relaxor ferroelectrics Na1/2Bi1/2TiO3 (NBT) and PbMg(1/3)Nb(2/3)O3 (PMN) - Kreisel, J; Bouvier, P; Dkhil, B; Chaabane, B; Glazer, A; Thomas, P; Welberry, T (2004)
The aim of the present paper is to review and briefly discuss recent experimental results on the effect of high pressure (p > 1.5 GPa) on relaxor ferroelectrics, exemplified by Na1/2Bi1/2TiO3 and PbMg1/3Nb2/3O3. The main result is that relaxor ferroelectrics present important polar and structural pressure-instabilities, which lead to both phase transitions of the average structure and considerable changes of the local structure. It is in particular the observation of a pressure-induced suppression of the relaxor characteristic X-ray diffuse scattering that points to important changes in the local order. The complementary use of Raman spectroscopy, X-ray diffraction and X-ray diffuse scattering allows the proposition of a mechanism for the observed changes.